History of Dentistry in Central Serbia - Jeremic Marko; Vukovic Ana; Markovic Dejan; Vukovic Rade; Stanojlovic Ninoslav (Balkan Stomatological Society, 2016)
History of dentistry in the Central Serbian District of Jagodina has been influenced by traditional medicine for centuries. Development of dentistry in the region of Jagodina was slow, the level of oral and general hygiene was low and the sanitary prevention was absent. Trained physicians started to practice medicine and dentistry in the first half of the nineteenth century and they were educated in abroad universities. However, common people used to address to these physicians only when the traditional medicine were unable to help. Until the end of the World War II, common, mostly rural people, with the urgent dental treatment need were usually referred to the barbers, healers or empirics in the nearby villages rather than the dentists. Medications used for the urgent dental treatment were balsams and solutions made of herbs. After the World War II, the dental technicians who finished special courses started to practice dentistry. In 1947 the Regional Dental Office in Jagodina was opened and in 1955 the first Doctor of Dental Medicine who graduated from the School of Dental Medicine of University of Belgrade was employed. Nowadays, the Department of Dentistry represents is an important and independent part of the Health Care Centre in Jagodina.